Exclusion testing in pregnancy for Huntington's disease. Issue 8 (August 1990) - Tyler, A; Quarrell, O W; Lazarou, L P; Meredith, A L; Harper, P S
Abstract : The results of DNA analysis are presented for a series of 90 couples, with one partner at 50% risk for Huntington's disease (HD), who were referred for exclusion testing in pregnancy over a three year period. Thirty-seven couples were studied in detail. The aims of the study were to evaluate attitudes towards prenatal testing, before pregnancy and afterwards, and the effectiveness of our counseling and methods of organising the service. Problems which could arise in relation to presymptomatic testing are documented. It is concluded that exclusion testing is a valuable form of prediction for some couples, particularly where family structure does not permit prediction for the person at risk. The need for intensive counselling was highlighted by the difficulties experienced by many couples in understanding how the test worked. Particular ethical and organisational problems may arise which require careful consideration beforehand and some recommendations are made. The proportion of couples who will continue to request exclusion testing as pre-symptomatic testing becomes more widely applicable remains unknown.